Practical statistics for field biology - Fowler, Jim 1943-; Cohen, Louis 1928-; Jarvis, Phil (John Wiley & Sons Ltd, 1998)
This expanded edition aims to provide biologists with sufficient grounding in statistical principles and methods to enable them to understand research reports in journals, decide on the most appropriate statistical tests for their own problems and finally to analyze and present their findings.